Literacy for the new millennium - Guzzetti, Barbara J. (Westport, Conn. Praeger, 2007)
Offers a comprehensive outline of the study and practice of literacy in the United States. This series features books that are divided into three sections: recent trends and issues impacting the field, issues in assessment and instruction, and issues outside the classroom that impact literacy development and practice.
v. 1. Early literacy -- v. 2 Childhood literacy -- v. 3 Adolescent literacy -- v. 4 Adult literacy.
Keywords: Literacy; Language arts